Corporate social responsibility in the digital age - Adi, Ana; Grigore, Georgiana; Crowther, David (Developments in corporate governance and responsibility ;, 2015)
Over the past half century, corporate social responsibility has become an important concept in management, marketing and communication literature. In the past twenty years a visible shift has been made into what was written about CSR: a move away from the financial benefits derived from such activities towards reputational impact, stakeholder relationships and communication with a wide range of audiences being note. With social and digital media reshaping the way in which business is conducted, and with the number of companies embracing the new social medium for their marketing and communication programmers, this book re-examines CSR practices from a digital perspective. In doing so, it revisits some of the theoretical discussions about CSR while inquiring whether and how CSR can be applied online. This book examines key conceptual insights about corporate social responsibility and digital and social media, and explores best practices for online CSR. In this way, the volume explores the impact and influence of the new social on responsibility and its feasibility, measurability and success in a boundary-less world.